ANSWER
![x = 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/72jcn4mo8f92gbbiktmv2n2bxqzgyrhhw5.png)
Step-by-step explanation
The given equation is
![√(3x + 7) = x - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/drhgiwiayze3o45b664464awnolund64v8.png)
We square both sides of the equation to obtain,
![(√(3x + 7) ) ^(2) =( x - 1)^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/srkl54gyvrq0f85kool0p8nfsrtl3gdvc9.png)
This implies that,
![3x + 7 = {x}^(2) - 2x + 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w0bhsiyxjst6lezxtj496s7e18ezy0lbq0.png)
Rewrite in standard quadratic equation form.
![{x}^(2) - 2x - 3x+ 1 - 7 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/3nompdaml4g46y68jpffcz0oexpav04739.png)
![{x}^(2) -5x - 6= 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/f0p0b0a4ji0lvltsb2b2y3eis8h2tpniz9.png)
Factor
![(x - 6)(x + 1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wxgvn6uwehx9d7a4kap6z2hqrflov5r0u2.png)
This implies that,
![x = 6 \: x = - 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rak0fuj29td5a21rk0yt6wxyz4jdtyciox.png)
We check for extraneous solution by substituting each x-value into the original equation.
When x=-1,
![√(3( - 1)+ 7) = - 1- 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ifeneg5qdy63suha5785xb25ystshwxxz.png)
![√(4) = - 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/zyni43z6fmkv8g6a3hjerts7u82fjy9qhb.png)
2=-2....False
Hence x=-1 is an extraneous solution.
When x=6,
![√(3( 6)+ 7) = 6- 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d3irf0gkrumgznd187csestga1ygvv9noi.png)
![√(25) = 5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/uf2zcxfuegclsc8wwik41ob0xethnka46f.png)
5=5 is True.
Hence x=6 is the only solution.